Ryzyko a controlling w przedsiębiorstwach realizujących projekty - Sieradzka-Widz, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Nowadays much more enterprises try to use project management. The building enterprises base their activity on building projects (building contracts). This article presents projects risk, project risk management and controlling as modern instrument thanks to which project-oriented enterprises can minimalize the risk.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 405-411